Adaptive expertise – a characteristic of expertise in outdoor instructors?. (3rd July 2020) - Mees, Alice; Sinfield, Dean; Collins, Dave; Collins, Loel
ABSTRACT: Background: Over the past 10 years, research has started to investigate the pedagogic practices of instructors and coaches working in adventure sports settings. Outdoor instructors face particular challenges regarding the impact the dynamic environment has on the coaching process and their students. This challenging combination of factors obliges the instructor to be agile in response. We propose that this adaptive expertise is characteristic of these factors and that adaptability may be a beneficial focus of outdoor instructor training and education. Purpose: The major aim was to identify if adaptive expertise is an attribute of outdoor instructors? And if so, what are its characteristics in this context? Research design and data collection : We applied a mixed methodology to a sample of outdoor instructors ( n  = 64). The instructors were asked to complete a quantitative adaptive expertise inventory. We then interviewed a selected sub-sample ( n  = 12). Participants and setting: Quantitative data was collected from outdoor instructors working in the UK ( n  = 64). The sample consisted of instructors qualified to work independently with groups in adventurous settings in a range of activities. Qualitative data was collected from a smaller sample ( n  = 12) via a series of thematically analysed semi-structured interviews. Findings: Results suggest that the participating outdoor instructors have high levels of adaptive expertise. A characteristic of that adaptive capacity is a combination of skills revolving around reflection, metacognition, and situational awareness. There were differences, however, between less and more experienced outdoor instructors in their adaptive capacity, with less experienced instructors being adaptive to a lesser extent. Conclusions: The implication is that further research is worthwhile to examine the development of instructors' adaptive capacity. The training and education of outdoor instructors requires pedagogic approaches that facilitate and engender adaptability, flexibility and agility in neophyte instructors.